Relevansi Teori Agensi dalam Ekonomi dan Manajemen Modern: Analisis Konseptual dan Implikasi Organisasional - Monariska Monariska; Edi Saputra; Jahimi Afrizalmi (Economia: Journal of Economics and Management, 2025)
This study aims to examine the relevance of Agency Theory in modern economics and management through a conceptual literature-based analysis. Agency Theory explains the contractual relationship between principals and agents, highlighting issues such as information asymmetry, moral hazard, and conflicts of interest. In contemporary organizational contexts characterized by increasing complexity, digital transformation, and dispersed ownership structures, agency problems remain highly significant. This paper employs a qualitative approach based on an extensive review of scholarly literature to analyze the theoretical foundations, developments, and practical implications of Agency Theory. The findings indicate that despite various criticisms and the emergence of alternative perspectives such as stewardship theory and stakeholder theory, Agency Theory continues to provide a robust analytical framework for understanding governance mechanisms, incentive alignment, monitoring systems, and organizational performance. Furthermore, the study underscores the importance of integrating behavioral and institutional dimensions to enhance the explanatory power of the theory. The article contributes to the enrichment of economic and management literature by reaffirming the strategic relevance of Agency Theory in designing effective organizational structures and governance practices in modern business environments. Abstrak Penelitian ini bertujuan untuk mengkaji relevansi Teori Agensi dalam ekonomi dan manajemen modern melalui analisis konseptual berbasis kajian pustaka. Teori Agensi menjelaskan hubungan kontraktual antara prinsipal dan agen, dengan menekankan permasalahan seperti asimetri informasi, moral hazard, dan konflik kepentingan. Dalam konteks organisasi kontemporer yang ditandai oleh kompleksitas yang meningkat, transformasi digital, dan struktur kepemilikan yang tersebar, permasalahan agensi tetap relevan. Penelitian ini menggunakan pendekatan kualitatif melalui telaah literatur ilmiah untuk menganalisis landasan teoretis, perkembangan, serta implikasi praktis Teori Agensi. Hasil kajian menunjukkan bahwa meskipun terdapat kritik dan munculnya perspektif alternatif seperti teori stewardship dan teori stakeholder, Teori Agensi tetap menjadi kerangka analitis yang kuat dalam memahami mekanisme tata kelola, penyelarasan insentif, sistem pengawasan, serta kinerja organisasi. Studi ini menegaskan pentingnya integrasi dimensi perilaku dan kelembagaan guna memperkuat daya jelaskan teori tersebut dalam lingkungan bisnis modern.